Policy of Lampung Province Regional Budget Policy on Improving Performance of Health Fields: Lower Nutrition And Low Birth Weight Loss - sutarto, sutarto; Bakri, samsul (Jurnal Niara, 2020)
Toddler children are a nutrition-prone group. so that if the nutritional intake is not as needed. Malnutrition in all its forms brings large direct and indirect costs to individuals. family and all countries. The purpose of this study is the relationship between the structure of the Lampung Province budget and the incidence of malnutrition and low birth weight during the last ten years. This study method uses a method of analyzing literature and documents, by comparing the regional budget with the incidence of malnutrition and LBW and accompanied by a graph of linear equations.The effect of the financing provided by the Lampung Regional Government in the form of the annual budget and regional income in Lampung Province over the past 9 years against the incidence of malnutrition and LBW has an impact on the decline in incidence. Decrease in malnutrition 7 toddlers per 1,000,000 toddlers and LBW decreased by 4 per 100,000 from the incident with the addition of 1 million rupiah.